3-Aminopropyltriethoxysilyl functionalized Na-Al-MCM-41 solid base catalyst for selective preparation of 2-phenylpropionitrile from phenylacetonitrile - Venkatesan, C.; Chidambaram, M.; Singh, A. P. (Applied Catalysis A-General, 2005)
Various solid base catalysts have been prepared by ion exchange of zeolites and Na-Al-MCM-41 and by organosilane grafting over mesoporous materials. Base catalysts thus synthesized were studied in the selective monomethylation of phenylacetonitrile (PAN) to 2-phenylpropionitrile (2-PPN) using dimethylcarbonate (DMC) as an alkylating agent in a Parr autoclave at a temperature ranging between 443 and 473 K and at autogenously developed pressure. NH2-Na-Al-MCM-41 (30) showed a high activity, and the optimum loading of 3-aminopropyltriethoxysilyl (3-APTES) was found to be 1.35 mmol g(-1), being consistent with the structural characterization. Co-condensation of 3-APTES, tetraethylorthosilicate (TEOS) and sodiumaluminate in the presence of surfactant provides a material with uniformly distributed basic sites responsible for high activity in the selective monomethylation of phenylacetonitrile. (c) 2005 Elsevier B.V. All rights reserved.
Keywords: 2-phenylpropionitrile; base catalysis; dimethylcarbonate; monomethylation; NH2-Na-Al-MCM-41; phenylacetonitrile

Organosilanesulfonic acid-functionalized Zr-TMS catalysts: synthesis, characterization and catalytic applications in condensation reactions - Chidambaram, M.; Venkatesan, C.; Singh, A. P. (Applied Catalysis A-General, 2006)
Organosilanesulfonic acid (-Si-R3S-R4SO3H, OSA)-functionalized mesoporous Zr-TMS (Zr-TMS-Si-R3S-R4SO3H, Zr-TMS-OSA) was synthesized either by post-synthetic modification of Zr-TMS (zirconia-based transition metal oxide mesoporous molecular sieves) with 3-mercaptopropyltrimethoxysilane (3-MPTS) and further with 1,4-butanesultone (1,4-BS) or by in situ one-pot synthesis procedure. A number of physico-chemical characterization techniques have been used to show that the organosilanesulfonic acid groups were anchored on to the walls of Zr-TMS. MCM-41-Si-R3S-R4SO3H-20 (MCM-41-OSA-20) was also prepared by post-synthesis procedure for comparison. Physico-chemical properties of in situ made A-Zr-OSA-20, Zr-TMS-SO3H-20 and MCM-41-OSA-20 were compared with Zr-TMS-OSA catalysts. The catalytic activity of the materials was tested in liquid phase condensation of aniline with p-formaldehyde to 4,4'-diaminodiphenylmethane (4,4'-DADPM). Results showed that Zr-TMS-OSA catalysts were more active than Zr-TMS-SO3H-20, MCM-41-OSA-20 and A-Zr-OSA-20 and more selective than Zr-TMS-SO3H-20 and A-Zr-OSA-20 catalysts. (C) 2006 Elsevier B.V. All rights reserved.
Keywords: Acid catalyst; condensation of aniline; mesoporous ZrO2; organic functionalization; organosilanesulfonic acid

Benzylsulfonic acid functionalized mesoporous Zr-TMS catalysts: an efficient and recyclable catalyst for the preparation of coumarin derivatives by pechmann condensation reaction - Selvakumar, S.; Chidambaram, M.; Singh, A. P. (Catalysis Communications, 2007)
Benzylsulfonic acid functionalized mesoporous Zr-TMS (Zr-TMS-BSA, Zr-TMS, zirconia based transition metal oxide mesoporous molecular sieves) catalyst is used as an alternative to conventional acid catalysts in the von Pechmann condensation of aromatic alcohols with ethyl acetoacetate leading to the formation of coumarin derivatives in solvent free condition at 150 degrees C. Three types of coumarins, 7-hydroxy-4-methylcoumarin (beta-methylumbelliferone), 7-methoxy-4-methylcoumarin (Methyl-4-methylumbelliferyl ether) and 7,8-benzo-4-methylcoumarin derivatives have been prepared using resorcinol, 3-methoxyphenol and 1-naphthol, respectively. The catalytic activity and the recycle studies of the catalyst in all the three reactions proved the superior performance of the catalyst. Further the products were confirmed by GC, elemental analysis, melting point and NMR techniques. Finally, the probable mechanism for Pechmarm condensation using Zr-TMS-BSA catalyst has been reported. (c) 2006 Elsevier B.V. All rights reserved.
Keywords: benzylsulfonic acid; Pechmann condensation and coumarins; Zr-TMS-BSA catalysts